Ma grande église et ma petite chapelle 150 ans d'affinités électives entre le Collège de France et l'École pratique des hautes études - Fournet, Jean-Luc (Passage des disciplines, 2020)
"Ma grande église et ma petite chapelle": this is how, in 1894, the eminent medievalist Gaston Paris referred to the two institutions at which he taught: the Collège de France and the École pratique des hautes études (EPHE). Founded respectively in 1530 and 1868, these two places of "science in the making" (Ernest Renan) have maintained almost symbiotic ties, as many scholars and professors have moved from one to the other or have worked simultaneously in both. It is on these elective affinities that this book, the product of a symposium organized at the Collège de France on the occasion of the EPHE's 150th anniversary, sheds light through studies on the history of these two institutions, reviews by discipline (comparative grammar, history of religions, anthropology, Sinology, Assyriology, Egyptology) and portraits of some key personalities (Ernest Renan, Gaston Paris, Abel Lefranc, Sylvain Lévi, Louis Robert). Beyond the anecdotal, prosopography or fortuitous institutional crossovers, these studies afford an opportunity to reflect on the joint role of these two institutions in the history of knowledge.